How Can a Growing Use of Clare’s Law Help Us Meet Human Rights Obligations to Victims of Domestic Abuse? - Grace, Jamie (feminists@law, 2024)
The Domestic Violence Disclosure Scheme (the DVDS, or 'Clare's Law') sees police forces warn members of the public, as 'applicants', about their possibly abusive partners. There were more than 25,000 more applications under 'Clare's Law', overall, in the year to March 2023 than in the year to March 2020 for England and Wales (namely, 45,344 applications compared to 20,147 – more than doubling the use of the Scheme in just three years). Disclosures also jumped from 8,715 in the year to March 2020, to 17,438 in the year to March 2021 (again a doubling of the use of disclosures). These statistics aside, the task of trying to establish how effective the DVDS is at protecting victims is still unfinished. This article seeks to establish whether, and if so, how the DVDS contributes to compliance with developing human rights law standards – drawing on a body of European and domestic case law and policy. From a feminist legal perspective, however, there remains a key issue that, however many more DVDS applications and disclosures are made in England and Wales year-on-year, and aside from the unknown efficacy of those disclosures in preventing domestic abuse, there has been a disturbing trend toward serious failures to protect victims from violence against women and girls, seen in decreasing prosecutions for domestic abuse, and specifically domestic abuse-related rape, in the same time frame.